Investigating EFL pre-service teachers’ pedagogical competence, challenges, and expectations in micro-teaching - Siti Mafulah; Eka Setyowati Febrianti (Journal on English as a Foreign Language)
Pre-service teachers should master pedagogical competence. Some studies focused on experienced teachers, and the studies exploring the pedagogical competence of pre-service teachers in micro-teaching classes are limited. Therefore, this study aims to investigate how the pedagogical competence that English as a foreign language (EFL) pre-service teachers mastered in micro-teaching classes as well as the challenges and expectations of EFL pre-service teachers in micro-teaching classes. This study employed a qualitative case study with five participants involved. Data were obtained from observation and interviews. The data were gathered through observation and interviews and then analyzed thematically. The results indicated that the pre-service teachers mostly had limitations in terms of pedagogical competence. The limitation was in terms of teaching activities, pre-service teachers-student interaction and the use of teaching material or media. Moreover, some challenges in the micro-teaching class were found. The challenges lay within the use of the target language, the limited time provided, and the lack of real class experience, opportunity, and materials. The study’s findings imply that micro-teaching class can be a useful experience for pre-service teachers before they face the real class and they can increase their capacity to be future teachers.